“El impacto de las redes sociales en la participación política: un estudio mixto en estudiantes universitarios de 18 a 20 años en la ciudad de Loja”. - Ruiz Jiménez, María Dolores (2024)
The study focuses on the impact of social media, particularly X and Instagram, on the political participation of university students aged 18 to 20 in Loja. It aims to comprehend how these platforms influence the political behavior of this demographic locally. Through surveys and interviews with electoral strategy experts, the use of social media among students was assessed, revealing a high frequency of usage, with a marked preference for Instagram over X. Young individuals engaging in political discussions on social media display a higher likelihood of engaging in conventional offline political activities, such as attending rallies or voting. Instagram emerges as a highly relevant platform, suggesting that political strategies should consider the dynamics of these networks to effectively engage with this demographic. In summary, the study underscores the crucial role of social media, especially Instagram, in the political participation of university students in Loja, providing a solid foundation for future research and political strategies aimed at this demographic segment. Keywords: Social Media, Political Participation, Political Behavior